The Pengaruh Edukasi Pop-Up Book Terhadap Pengetahuan Konsumsi Buah Dan Sayur Pada Anak Usia Dini - Pratiwi, Syadz'a Putrianty; Herdhianta, Dhimas (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2024)
Background: Many people in Indonesia still ignore the role of PHBS in their daily lives. The lack of implementation of PHBS can have a negative impact on health. This can occur one of them because of changes in lifestyle such as reduced public interest in consuming fruits and vegetables. Riskesdas data in 2018 in Indonesia the lack of consumption of fruits and vegetables in the population aged ≥5 years is 95.5%, data in West Java is 98.2% and in the Cimahi City Region people only consume 23 grams/day. Therefore, it is necessary to educate about fruit and vegetable consumption in early childhood. Methods: This study used a quasy experiment design one group pretest-postest design. Sample used total sampling of 32 respondents. Data analysis Paired T-test. Results: Average score of respondents' knowledge before the intervention was 68.59 and the average score of respondents' knowledge after the intervention was 87.66. There was an increase in knowledge by 27.8%. The p value in this study was (p=0.000). Conclusion: There is an effect of giving Pop-Up Book media on knowledge of fruit and vegetable consumption in early childhood at PAUD Nusa Indah Cimahi City. Keywords: Pop-Up Book; Knowledge; Fruit and vegetable consumption; Early childhood